(untitled) - Parsons, Timothy R. (Oxford, 1995)
his popular undergraduate textbook offers students a firm grounding in the fundamentals of biological oceanography. As well as a clear and accessible text, learning is enhanced with numerous illustrations including a colour section, thorough chapter summaries, and questions with answers and comments at the back of the book.
Keywords: Marine ecology,Marine plankton,Primary productivity (Biology)